A A Systematic Literature Review on Visual Novel as an Engaging Medium for Learning English Skills - Putri, Athaya Rewanda; Yamin, Moh; Elyani, Eka Puteri (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Visual novels represent an innovative approach to language learning, particularly in enhancing reading comprehension and expanding vocabulary in English. This qualitative research investigates the impact of visual novels on various language competencies, including reading comprehension, vocabulary expansion, and motivation for language learning. The research approach used in this study is qualitative and systematic literature review (SLR) method to identify and evaluate relevant studies on visual novels as an engaging media for learning English skills. The five previous studies that discuss similar topics were collected as a data collection tool. The data collected from previous studies used are in the range of 2015-2023. The study's findings indicate that visual novels serve as a promising and helpful tool for individuals seeking to improve their language skills. The findings highlight the numerous advantages of visual novels, such as increased motivation, better reading comprehension, and improved vocabulary acquisition. The study highlights the potential of visual novels as valuable tools in language education, emphasizing their ability to make language learning enjoyable, engaging, and applicable to real-life contexts. Through their narrative-driven gameplay and immersive multimedia elements, visual novels offer learners an interactive and captivating learning experience. The integration of cultural aspects within visual novels further enriches the language-learning process, fostering deeper engagement and meaningful connections with the language. Additionally, the structure of visual novels accommodates diverse learning styles and proficiency levels, promoting motivation among learners. Furthermore, the interactive aspect of visual novels offers learners an exciting environment for language acquisition that is both engaging and enjoyable.